Konkurencyjność polskich przedsiębiorstw w przededniu przystąpienia do Unii Europejskiej - Adamczyk, Marzena; Piasecka, Agnieszka (Competitiveness of Polish Com panies the day Before Accession to European Union, 2005)
This article presents the general situation of Polish companies, problems they face and opportunities which gives European Single Market. In order to reach high competitive position Polish companies need to comply with EU standards. It would enable them on one hand to gain external benefits due to mutual penetration of economic effects as well as gain internal benefits that lead to development and possibility to expand. These benefits in due course lead to growth of Polish companies competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 20-30